2018
DOI: 10.1080/07420528.2018.1486851
|View full text |Cite
|
Sign up to set email alerts
|

Circadian system responses to nocturnal and diurnal hosts in the kissing bug,Triatoma infestans

Abstract: Insects express diverse behavioral rhythms synchronized to environmental cycles. While circadian entrainment to light-dark cycles is ubiquitous in living organisms, synchronization to non-photic cycles may be critical for hematophagous bugs that depend on rhythmic hosts. The purpose was to determine whether Triatoma infestans are capable of synchronizing to the circadian rhythms of potential hosts with temporally distinct activity patterns; and, if so, if this synchronization occurs through masking or entrainm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
6
1
Order By: Relevance
“…The various species of triatomines occupy specific geographic distributions, defined in part by their natural habitats within different regions and biomes on the American continent [2][3][4][5][6][7] . Distinct species of triatomines transmit T. cruzi with varying efficiency, defined by the insects' behavior, physiology and adaptation to the human domicile [8][9][10][11] . After an intensive utilization of pyrethroid insecticides in endemic areas in Brazil, the transmission of Chagas disease by triatomines (mainly Triatoma infestans) was virtually eliminated in many States 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The various species of triatomines occupy specific geographic distributions, defined in part by their natural habitats within different regions and biomes on the American continent [2][3][4][5][6][7] . Distinct species of triatomines transmit T. cruzi with varying efficiency, defined by the insects' behavior, physiology and adaptation to the human domicile [8][9][10][11] . After an intensive utilization of pyrethroid insecticides in endemic areas in Brazil, the transmission of Chagas disease by triatomines (mainly Triatoma infestans) was virtually eliminated in many States 12 .…”
Section: Introductionmentioning
confidence: 99%
“…This high-number rodent result, contrasts with the one-rodent experiment of Lopez et al, 19 where in the latter, insects only showed modulation of their rhythmicity, reinforcing the idea that more rodents may imply in a stronger synchroniser. Domestic triatomine species tend to be more present in rural dwellings with a higher proportion of humans and/or domestic animals (chickens, goats, dogs, etc.)…”
Section: Discussionmentioning
confidence: 45%
“…Our Lab has a colony in which individual activity is constantly recorded, a fact that strongly facilitated the logistics of the present experiment; (c) In the field, diurnal tuco-tucos 24 share the same habitat with nocturnal T. infestans ; (d) In Lab, fasted kissing bugs have been monitored feeding on tuco-tucos during the light phase (Abrahan L and Tachinardi P, unpublished observations); (e) In the laboratory setup, the daily activity of a single tuco-tuco in close proximity, has been shown to modulate the activity of triatomines. 19 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations